2008
DOI: 10.1094/cm-2008-0701-01-rv
|View full text |Cite
|
Sign up to set email alerts
|

Role of Winter Annual Weeds as Alternative Hosts for Soybean Cyst Nematode

Abstract: Soybean cyst nematode (Heterodera glycines Ichinohe, SCN) has been reported to parasitize a broad range of host plants, encompassing nearly 150 legume and non‐legume genera representing 22 plant families. Several SCN host species are common winter annual weeds in US soybean production fields and include purple deadnettle (Lamium purpureum L.), henbit (Lamium amplexicaule L.), field pennycress (Thlaspi arvense L.), shepherd's purse [Capsella bursa‐pastoris (L.) Medik], common chickweed [Stellaria media (L.) Vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Winter annual weeds have become prolific in United States agriculture because of the increased adoption of conservation tillage practices (Swagata et al 2009), widespread adoption of glyphosateresistant crops (Owen and Zelaya 2005), and the reduced use of residual herbicides (Shaner 2000). The impacts of winter annual weeds in cropping systems are often overlooked because these weeds complete their life cycle before, or at, crop sowing (Johnson et al 2008). However, dense mats of winter annual weeds may result in delayed soil warming in spring (Lee and Witt 2001), direct and indirect competition for water and nutrients during initial establishment of the main crop (Bernards and Sandell 2011), and difficult planting operations (Krausz et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Winter annual weeds have become prolific in United States agriculture because of the increased adoption of conservation tillage practices (Swagata et al 2009), widespread adoption of glyphosateresistant crops (Owen and Zelaya 2005), and the reduced use of residual herbicides (Shaner 2000). The impacts of winter annual weeds in cropping systems are often overlooked because these weeds complete their life cycle before, or at, crop sowing (Johnson et al 2008). However, dense mats of winter annual weeds may result in delayed soil warming in spring (Lee and Witt 2001), direct and indirect competition for water and nutrients during initial establishment of the main crop (Bernards and Sandell 2011), and difficult planting operations (Krausz et al 2003).…”
mentioning
confidence: 99%
“…Winter annual weeds are more susceptible to herbicide treatments in the fall or early spring, when they are small. During late spring, herbicide application may not result in the desired control if the weeds are at an advanced growth stage (Johnson et al 2008). Little research has focused on using the time of winter annual weed emergence to make weed management decisions (Cici and Van Acker 2009).…”
mentioning
confidence: 99%
“…Furthermore, winter annual weeds are more susceptible to herbicide treatments in the fall when they are small. During spring, herbicide application might not result in the desired control if these weeds are at an advanced growth stage (Johnson et al 2008), and SCN reproduction may no longer be prevented or reduced (Werle et al 2013).…”
Section: Description Of Simulationmentioning
confidence: 99%
“…Winter annual weeds are more susceptible to herbicide treatments in the fall when they are small, but herbicides should only be sprayed when environmental conditions are favorable for both operational application and foliar uptake Hasty et al 2004). During late spring, herbicide application might not result in desired control because these weeds are at an advanced growth stage (Johnson et al 2008). Also, Creech et al (2007b) found that the majority of SCN reproduction on winter annual weeds occurred during the fall.…”
mentioning
confidence: 99%
“…This suggests that fall management of winter annual weeds might be the most effective way to minimize potential reproduction of SCN on these weed species. Thus, failure to manage winter annual weeds could provide an additional niche for SCN to develop and increase its population density in the absence of soybean (Johnson et al 2008).…”
mentioning
confidence: 99%